Optimized Intracellular Staining Reveals Heterogeneous Cytokine Production Ability of Murine and Human Hematopoietic Stem and Progenitor Cells - Luo, Shufeng; Lin, Huiling; Zhu, Lan; Chen, Hai-Tian; Yang, Siqian; Li, Jinheng; Liu, Mingyu; Zheng, Limin; Wu, Chong (Frontiers in Immunology, 2021)
Under stress conditions, hematopoietic stem and progenitor cells (HSPCs) can translate danger signals into a plethora of cytokine signals. These cytokines, or more precisely their combination, instruct HSPCs to modify the magnitude and composition of hematopoietic output in response to the threat, but investigations into the heterogeneous cytokine expression and regulatory mechanisms are hampered by the technical difficulty of measuring cytokine levels in HSPCs at the single-cell level. Here, we optimized a flow cytometry-based method for the simultaneous assessment of multiple intracellular cytokines in HSPCs. By selecting an optimal combination of cytokine restimulation reagents, protein transport inhibitors, and culture conditions, an optimized restimulation condition for intracellular staining was developed. Using this method, we successfully examined expression levels of granulocyte/macrophage colony-stimulating factor (GM-CSF), interleukin-6 (IL-6), and tumor necrosis factor-α (TNF-α) in murine and human HSPC subsets under steady-state or different stress conditions. Different cytokine expression patterns were observed, suggesting distinct regulatory modes of cytokine production dependent on the HSPC subset, cytokine, disease, organ, and species. Collectively, this technical advance may help to obtain a better understanding of the nature of HSPC heterogeneity on the basis of differential cytokine production.